Effect of Redox Time on Carbon Based Purity Made from Coconut Shell Simple Carbonization - Zain Asrori; Lailatin Nuriyah; Djoko H Santjojo; Masruroh Masruroh (Natural B, Journal of Health and Environmental Sciences, 2013)
Purification of carbon from coconut shell has been done by redox reaction method. Carbon was produced with simple heating carbonization method at 700 °C. Oxygen reduction process from the carbon was carried at temperature of 350 °C for 200 mL/min and 300mL/min with the H2 flow rate for 60 min, 120 min, and 180 min. Synthesis of carbon through simple heating carbonization method obtaining (93.84 ± 2.21) % of carbon content. Redox time optimization method successfully increased levels of carbon purity up (97.87 ± 1.47) %. The increase in carbon content was caused by the loss of a functional group with carbon-oxygen bond (C-O) and sulfur (S-O), as evidenced from FTIR test results.